2018
DOI: 10.1007/s00344-018-9807-x
|View full text |Cite
|
Sign up to set email alerts
|

Tendril Coiling in Grapevine: Jasmonates and a New Role for GABA?

Abstract: Grapevine (Vitis vinifera L., Vitaceae) belongs to the genus Vitis, and is characterized as a vine due to the presence of tendrils, which are located opposite to leaves. Tendrils are thigmo-responsive organs, able to carry out delicate mechanosensory responses upon touch and related stimuli. These organs are an adaptation of the plant to climb with the help of support to higher places and finally remain at a position with favorable light quality. In previous studies on Bryonia dioica (Cucurbitaceae), phytohorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Increasing GABA production in guard cells reduces stomatal opening and transpiration, and regulating the release of tonoplast-localized anion transporters improves water use efficiency and drought tolerance [10,81]. The drought stress tolerance of various plant species, such as apples [82], tomatoes [83], and grapevines [84], can be improved by applying exogenous GABA, as demonstrated in previous studies. The optimal dosage and application method of GABA for achieving maximum drought stress tolerance may differ depending on the plant species and environmental conditions.…”
Section: Application Of Gaba To Alleviate the Effects Of Drought Stressmentioning
confidence: 67%
“…Increasing GABA production in guard cells reduces stomatal opening and transpiration, and regulating the release of tonoplast-localized anion transporters improves water use efficiency and drought tolerance [10,81]. The drought stress tolerance of various plant species, such as apples [82], tomatoes [83], and grapevines [84], can be improved by applying exogenous GABA, as demonstrated in previous studies. The optimal dosage and application method of GABA for achieving maximum drought stress tolerance may differ depending on the plant species and environmental conditions.…”
Section: Application Of Gaba To Alleviate the Effects Of Drought Stressmentioning
confidence: 67%
“…2008, 2012, Malabarba et al. 2019). These substances are probably the reason that thigmomorphogenetic effects can be induced in tissue regions far from where a mechanical stimulus was actually applied (Erner et al.…”
mentioning
confidence: 98%
“…When the signals generated in response to mechanical stimulation ultimately influence growth and development, the entire physiological process, from stimulus detection to ultimate response, is referred to as thigmomorphogenesis (Jaffe 1973). Phytohormones are thought to be among the various signaling molecules involved in mediating this process (e.g., Erner and Jaffe 1982, Biro and Jaffe 1984, Chehab et al 2008, Malabarba et al 2019. These substances are probably the reason that thigmomorphogenetic effects can be induced in tissue regions far from where a mechanical stimulus was actually applied (Erner et al 1980, Coutand et al 2000.…”
mentioning
confidence: 99%
“…4 Therefore, ABA biosynthesis, catabolism and signaling are dependent on the cultivar and 5 also on the ripening stage. Recently, the short-term effects of ABA on different organs of 6 grapevine were studied and showed that the responses of each organ were unique 7 indicating that ABA signaling varies with the organ [58,59]. It may be that it also varies 8 with the tissue; therefore differences in ABA metabolism between skin and pulp may 9 partially account for the differences noticed here between the whole berries of the two 1 0 cultivars.…”
Section: Phenotypic Characterization Of Infected and Mock-treated Gramentioning
confidence: 94%